Dispositional Mindfulness and Attentional Control: The Specific Association Between the Mindfulness Facets of Non-judgment and Describing With Flexibility of Early Operating Orienting in Conflict Detection - Sørensen, Lin; Osnes, Berge; Visted, Endre; Svendsen, Julie Lillebostad; Adolfsdottir, Steinunn; Binder, Per-Einar; Schanche, Elisabeth (Frontiers in Psychology, 2018)
Background: A state of mindfulness refers to a present-centered attentional awareness without judging. Being mindful seems to increase the ability to be flexible and adaptive in attention focus according to situational contingencies. The way mindfulness affects such attentional control is often measured with three different but interacting attentional networks of alerting (preparedness), orienting (selection of stimulus), and conflict detection (suppression of non-irrelevant stimuli). In the current study, the aim was to study the effects of dispositional mindfulness on these attention networks, and specifically the effects on the interactions between these attention networks. Methods: Fifty participants between 19 and 29 years old filled out the questionnaire Five Facet Mindfulness Questionnaire (FFMQ) and performed the revised version of the Attention Network Test (ANT-R). The five FFMQ facets of Describing, Non-Judgment, Orienting, Non-Reactivity, and Acting with Awareness were included as predictors in multiple linear regression analyses with the ANT-R scores of alerting, orienting, conflict detection, and the interaction scores of alerting by conflict detection and orienting by conflict detection as outcome variables, respectively. Results: Higher dispositional mindfulness as measured with the five FFMQ facets predicted lower interaction scores (lower reaction times) of orienting by conflict detection, and none of the other ANT-R scores. It was specifically the FFMQ facets of Describing and Non-Judgment that predicted this lower interaction score of orienting by conflict detection. Conclusion: Our findings indicate that being mindful associates with a more flexible and efficient orienting attention. It associates with a higher ability to disengage from salient stimuli that is irrelevant to pursue goal-directed behavior (conflict detection).